Shariah Regulations for Environmental Protection and Their Role in Building Sustainable Behavior among Students of Knowledge (Al-Farooq Journal of Sciences, 2026)
This study aims to examine the Shariah regulations governing environmental protection and their role in fostering sustainable behavior among students of knowledge. It explores Islamic legal texts and jurisprudential principles related to the preservation and sustainability of natural resources and links them to the concepts of green education and sustainable development. The research problem arises from the gap between theoretical awareness of Islamic environmental teachings and their practical application within educational institutions. The study employed an inductive approach to investigate relevant Islamic texts and legal maxims, alongside a descriptive-analytical approach to examine the dimensions of sustainable environmental behavior and its educational implications. The findings revealed that Islamic Shariah provides a comprehensive framework for environmental protection through principles such as the prohibition of wastefulness, prevention of harm, conservation of resources, and the promotion of land cultivation and environmental stewardship. These principles contribute significantly to shaping environmentally responsible behavior among students. The study further highlights the importance of integrating Shariah-based environmental values into educational curricula and university activities, while transforming educational institutions into practical green learning environments that support sustainability goals. The study recommends strengthening interdisciplinary research between Islamic and environmental sciences and developing awareness programs that promote a culture of environmental sustainability within educational institutions.
Keywords: Shariah Regulations, Environmental Protection, Sustainable Behavior, Green Education, Students of Knowledge